Formulation of human–structure interaction system models for vertical vibration. (1st September 2016) - Caprani, Colin C.; Ahmadi, Ehsan
Abstract: In this paper, human–structure interaction system models for vibration in the vertical direction are considered. This work assembles various moving load models from the literature and proposes extension of the single pedestrian to a crowd of pedestrians for the FE formulation for crowd–structure interaction systems. The walking pedestrian vertical force is represented as a general time-dependent force, and the pedestrian is in turn modelled as moving force, moving mass, and moving spring–mass–damper. The arbitrary beam structure is modelled using either a formulation in modal coordinates or finite elements. In each case, the human–structure interaction (HSI) system is first formulated for a single walking pedestrian and then extended to consider a crowd of pedestrians. Finally, example applications for single pedestrian and crowd loading scenarios are examined. It is shown how the models can be used to quantify the interaction between the crowd and bridge structure. This work should find use for the evaluation of existing and new footbridges.